Quantitative analysis of nighttime effects of radiation belt energetic electron precipitation on the D-region ionosphere during lower solar activity periods - X. Dong; X. Dong; X. Dong; S. Zhao; S. Zhao; S. Zhao; L. Liao; W. Xu; R. Lin; R. Lin; R. Lin; X. Sun; et al. (Atmospheric Chemistry and Physics)
Energetic electron precipitation (EEP) from the Earth's radiation belts can ionize neutral molecules in the D-region ionosphere (60–90 km altitude), significantly influencing the conductivity and chemical species therein. However, due to the limited resolution of space-borne instruments, the energy and fluxes of electrons that truly precipitate into the atmosphere still remain poorly investigated. To resolve this problem, in this study, we have utilized the wave and particle data measured by the Electric Field Detector (EFD) and High-Energy Particle Detector (HEPP) on board the China Seismo-Electromagnetic Satellite (CSES-01) during nighttime conditions between 2019 and 2021. Using the measurements of extremely low frequency (ELF) waves, we have derived the reflection height of the D-region ionosphere, which turn out to be highly consistent with the electron and X-ray measurements of the CSES. Our results show that the influence of EEP on the two hemispheres is asymmetric: the reflection height in the Northern Hemisphere is in general lowered by 2.5 km, while that in the Southern Hemisphere is lowered by 1.5 km, both of which are consistent with first-principles chemical simulations. We have also found that the decrease in reflection height exhibits strong seasonal variation, which appears to be stronger during wintertime and relatively weaker during summertime. This seasonal difference is likely related to the variation of the background ionospheric electron density. Our findings provide a quantitative understanding of how EEP influences the lower ionosphere during solar minimum periods, which is critical for understanding the magnetosphere–ionosphere coupling and assessing the impact on radio wave propagation.